Perilaku Warga Peduli AIDS terhadap Penanggulangan HIV dan AIDS Di Kota Kupang - Fernandez, Wenzel; Manurung, Imelda February Ester; Toy, Sarcy M; Ndoen, Honey I (Husada Mahakam, 2019)
The AIDS Tackling Committee (KPA) of KupangCity has been running several programs handling over the AIDS and HIV. One of the program is involving ordinary member of the society through AIDS Care Community Member. This research aim is to describe knowledge, attitude, and behavior of AIDS Care Community Members towards HIV and AIDS Tackling Program. This research is a survey, descriptive in nature. It was held from October 2017 to March 2018. The research population is 625. By using Slovin formula and simple random sampling technique, the sample is 93. The research results are as follows: the majority of the community member possessed a good knowledge (74%), all of the community members (100%) showed a positive attitude on the effort and 60,2% of the members of the community have conducted supportive acts towards the effort.  Therefore, it is suggested that, there should be some upgrading’s on cadres capacity, especially their active involvement in mobilizing the society to conduct some supportive acts. Finally, it is expected that the overall society participation in tackling HIV and AIDS should be uplifted. Keywords: AIDS Care Community Members, Behavior Salah satu program penanggulangan HIV dan AIDS yang dicanangkan oleh KPA Kota Kupang adalah pelibatan masyarakat umum melalui Warga Peduli AIDS. Tujuan penelitian adalah mengetahui gambaran pengetahuan, sikap, dan tindakan warga peduli AIDS terhadap upaya penanggulangan HIV dan AIDS Kota Kupang. Jenis penelitian ini adalah penelitian survei deskriptif, waktu penelitian dilaksanakan dari bulan Oktober sampai dengan bulan Maret 2018. Besar populasi penelitan 625 orang dan besar sampel 93 orang yang diperoleh dari rumus Slovin.  Teknik pengambilan sampel yang digunakan adalah teknik simple random sampling. Hasil penelitian menunjukkan gambaran pengetahuan Warga Peduli AIDS terhadap penanggulangan HIV dan AIDS mayoritas Warga Peduli AIDS berpengetahuan baik (74,2%). Gambaran sikap Warga Peduli AIDS terhadap Penanggulangan HIV dan AIDS semua Warga Peduli AIDS bersikap positif (100%). Gambaran tindakan Warga Peduli AIDS terhadap Penanggulangan HIV dan AIDS mayoritas Warga Peduli AIDS sudah melakukan tindakan yang mendukung penanggulangan HIV dan AIDS (60,2%). Diharapkan agar adanya peningkatan kapasitas kader-kader mengenai keterlibatan aktif dalam upaya memobilisasi masyarakat mengenai tindakan- tindakan Peduli AIDS, serta bagi masyarakat untuk meningkatkan partisipasi dalam upaya menanggulangi AIDS di wilayah Warga Peduli AIDS. Keyword: Perilaku, Warga, Peduli, AIDS